MANAJEMEN STRATEGIK KEPALA SEKOLAH DALAM MENINGKATKAN MINAT SISWA KELAS XII UNTUK MELANJUTKAN PENDIDIKAN - Yudianto, Yudianto; Haryani, Sri; Yoseptry, Ricky; Nurlaela, Narti (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The aim of this research is to obtain an overview or information about how school principal management is implemented and its influence in increasing the interest of class This research uses management theory from G.R. Terry as a theoretical tool to see how the principal's strategic management is applied regarding the problem of the lack of interest of class XII students to continue to college. This research uses a qualitative method where the researcher aims to get an in-depth picture of the research problem using observation, interviews and study of school documents. The results of the research showed the decreasing interest of class XII to continue their study at SMA Al Qona’ah Baleendah is responded by the principal by making some strategies to increase their interest. The strategizes are expected could increase the interest of class XII students to continue their study at the higher level